Isolation and identification of bacterial pathogens causing ice-ice disease in Eucheuma cottonii seaweed at Seira Island Waters, Tanimbar Islands District, Maluku, Indonesia - NOVIANTY C. TUHUMURY; JACQUELINE M. F. SAHETAPY; JOLEN MATAKUPAN (Society for Indonesian Biodiversity, 2024)
Abstract. Tuhumury NC, Sahetapy JMF, Matakupan J. 2024. Isolation and identification of bacterial pathogens causing ice-ice disease in Eucheuma cottonii seaweed at Seira Island Waters, Tanimbar Islands District, Maluku, Indonesia. Biodiversitas 25: 964-970. Seaweed cultivation has proven to be beneficial and enhances the well-being of communities. Production of seaweed in the waters of Maluku has increased despite facing the problem of ice-ice disease. Therefore, this research aimed to isolate and identify bacteria on the Eucheuma cottonii seaweed species affected by ice-ice disease in the waters of Seira Island, Tanimbar Islands District, Maluku. It was conducted in August 2023 at three observation stations, and water quality samples were collected in situ at all three stations, including temperature, salinity, pH, dissolved oxygen (DO), and turbidity. Furthermore, bacterial isolation and identification were carried out at the Laboratory of Marine Aquaculture, Ambon. Bacteria isolation and purification were performed on TCBS media using the streak plate technique, while identification used the API 20E test. The results showed that water quality parameters supported seaweed growth. Four bacteria that caused ice-ice disease in the waters of Seira were identified as Vibrio alginolyticus, Vibrio fluvalis, Vibrio cholerae, and Aeromonas caviae. Moreover, all four bacteria found were gram-negative and pathogenic. Bacteria belonging to the genera Vibrio and Aeromonas have been proven to cause infections in marine organisms, including seaweed. In conclusion, four types of bacteria were identified in seaweed affected by ice-ice disease.